SISTEM PEMETAAN DAN REKOMENDASI UNTUK OBJEK WISATA DI KABUPATEN BOYOLALI BERDASARKAN SIG (SISTEM INFORMASI GEOGRAFIS) - Ferry Illham Setiawan; Muqorobin Muqorobin; Tino Feri Efendi (Journal of Information System and Artificial Intelligence, 2025)
Boyolali Regency has various interesting tourist attractions, but limited information and tourist recommendations are an obstacle for tourists in planning a visit. Geographic Information System (GIS) can be a solution to present tourist location information visually and provide recommendations based on certain criteria such as distance, tourist category, and popularity. This research aims to develop a GIS that is able to recommend tourist attractions in Boyolali Regency. By utilizing spatial data and interactive features, this system is expected to facilitate tourists in finding and selecting tourist destinations that suit their preferences. The implementation results show that this GIS is effective in providing tourism recommendations and improving the accessibility of tourism information in Boyolali.